Strategic Insights into Elevating Marketing Performance - Farida (Yayasan Ilomata, 2023)
This research aims to determine the strategies used by the Melati Farming Women's Group in Bogor to improve product marketing performance. This article presents strategic insights into the marketing performance of the sweet potato brownie business through a mixed methodology approach. Data collected in research consists of primary data and secondary data. Primary data was obtained through observations and interviews in the form of prices produced and costs incurred to operate the business to gain profits, and secondary data was obtained from publications from related agencies, various print and online media, books, and literature related to research. The data collection method in this research used interviews, observation and documentation. The results of this research show that through the application of strategic management practices, such as international standardization with the SQF Code, product innovation, and response to global trends, this group has created a strong basis for expanding their business into international markets, even though on a relatively small scale. Based on the results of processing the IFE matrix, the total score is 3.11. This illustrates that the sweet potato brownie product business is a strong company internally, and based on the EFE matrix processing results in the table above, the resulting total score is 3.11. This illustrates that the KWT Melati sweet potato brownie business has solid external business opportunities.